2014
DOI: 10.1371/journal.pone.0087444
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Induces Resistance by Triggering Differentiation of Testicular Embryonal Carcinoma Cells

Abstract: Although testicular germ cell tumors are generally quite responsive to treatment with cisplatin, a small fraction of them acquire resistance during therapy. Even when cisplatin treatment is successful the patient is often left with a residual teratoma at the site of the primary tumor suggesting that cisplatin may trigger differentiation in some tumors. Using the human embryonal carcinoma cell line NTera2/D1, we confirmed that exposure to the differentiating agent retinoic acid produced a reduction in pluripote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Additionally, the slightly increased cisplatin-resistance observed following blockage of both Nodal and Activin signalling (using the high dose of SB431542), but not after specific inhibition of Nodal signalling, could indicate some redundancy between the Nodal and Activin pathways. We speculate that inhibition of Nodal signalling promotes downregulation of pluripotency factor expression in the malignant germ cells driving them towards a more differentiated phenotype, which is associated with reduced cisplatin-sensitivity [8][9][10][11][12]. However, since both ECs (high Nodal expression) and SEMs (low Nodal expression) are highly sensitive to cisplatin-based treatment [6,7], this may explain why we did not find pronounced effects on cisplatin-sensitivity upon manipulation of the Nodal signalling pathway.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, the slightly increased cisplatin-resistance observed following blockage of both Nodal and Activin signalling (using the high dose of SB431542), but not after specific inhibition of Nodal signalling, could indicate some redundancy between the Nodal and Activin pathways. We speculate that inhibition of Nodal signalling promotes downregulation of pluripotency factor expression in the malignant germ cells driving them towards a more differentiated phenotype, which is associated with reduced cisplatin-sensitivity [8][9][10][11][12]. However, since both ECs (high Nodal expression) and SEMs (low Nodal expression) are highly sensitive to cisplatin-based treatment [6,7], this may explain why we did not find pronounced effects on cisplatin-sensitivity upon manipulation of the Nodal signalling pathway.…”
Section: Discussionmentioning
confidence: 85%
“…The relationship between expression of pluripotency factors and cisplatin-sensitivity has also been examined in a TGCT-derived EC cell line, in which loss of pluripotency factor expression by siRNAmediated knockdown of OCT4, resulted in decreased sensitivity to cisplatin [9]. Moreover, treatment with retinoic acid to induce differentiation of the EC-derived NTera2 cell line along the neuroectodermal lineage, resulted in decreased expression of the pluripotency factor OCT4 and increased cisplatin-resistance [10][11][12], thus supporting the association between pluripotency factor expression and cisplatin-sensitivity. Although cisplatin-based chemotherapy has provided high cure rates for TGCTs, the treatment regimen is associated with long-term complications, including cardiovascular side effects and infertility as well as relapse [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…4e, Supplementary Table 7). Taken together, chemotherapy-resistant germ-cell tumours are associated with continued progression of RLOH copy number events and loss of pluripotency markers in this clinical cohort, although it is uncertain whether the loss of pluripotency markers is a driver of chemoresistance 11,28 , a marker of methylation changes in a further differentiated histology post-chemotherapy 29 , or a feature of both processes.…”
mentioning
confidence: 87%
“…Other groups have reported that loss of Oct4 expression leads to resistance in EC cells (Mueller et al ., , ; Koster et al ., ). Events that in addition to differentiation induced by RA can lead to down‐regulation of Oct4 are hypoxia (Wu et al ., ) and cisplatin treatment (Abada & Howell, ). All of these are known to have a negative impact on cisplatin sensitivity (Koch et al ., ; Abada & Howell, ), which is most likely mediated not only by down‐regulation of Noxa and Puma but also down‐regulation of miR‐17/‐106b family members, in turn leading to activation of p21 (Koster et al ., ).…”
Section: Resistance and Cellular Differentiationmentioning
confidence: 99%